Narrow-Leafed Lupin (Lupinus angustifolius L.) Seeds Gamma-Conglutin is an Anti-Inflammatory Protein Promoting Insulin Resistance Improvement and Oxidative Stress Amelioration in PANC-1 Pancreatic Cell-Line - Elena Lima-Cabello; Juan D. Alché; Sonia Morales-Santana; Alfonso Clemente; Jose C. Jimenez-Lopez (MDPI AG, 2019)
(1) Background: Inflammation molecular cues and insulin resistance development are some of the main contributors for the development and advance of the pathogenesis of inflammatory-related diseases; (2) Methods: We isolated and purified γ-conglutin protein from narrow-leafed lupin (NLL or blue lupin) mature seeds using affinity-chromatography to evaluate its anti-inflammatory activities at molecular level using both, a bacterial lipopolysaccharide (LPS)-induced inflammation and an insulin resistance pancreatic cell models; (3) Results: NLL γ-conglutin achieved a plethora of functional effects as the strong reduction of cell oxidative stress induced by inflammation through decreasing proteins carbonylation, nitric oxide synthesis and inducible nitric oxide synthase (iNOS) transcriptional levels, and raising glutathione (GSH) levels and modulation of superoxide dismutase (SOD) and catalase enzymes activities. γ-conglutin induced up-regulated transcriptomic and protein levels of insulin signalling pathway IRS-1, Glut-4, and PI3K, improving glucose uptake, while decreasing pro-inflammatory mediators as iNOs, TNFα, IL-1β, INFγ, IL-6, IL-12, IL-17, and IL-27; (4) Conclusion: These results suggest a promising use of NLL γ-conglutin protein in functional foods, which could also be implemented in alternative diagnosis and therapeutic molecular tools helping to prevent and treat inflammatory-related diseases.